THE ROLES OF SCHOOL ADMINISTRATORS IN PROMOTING INTERNAL QUALITY ASSURANCE OF THE EDUCATIONAL INSTITUTIONS OF SMALL SCHOOLS AS PERCEIVED BY TEACHERS UNDER THE OFFICE OF NAKHON RATCHASIMA PRIMARY EDUCATIONAL SERVICE AREA 2 - yangklang , Wirinya; Rattanawaraha, Worasit (Journal of MCU Nakhondhat, 2023)
The purposes of this research were 1) to study the role of school administrators in promoting quality assurance within the educational institutions of small schools according to teachers’ opinions under the office of Nakhon Ratchasima Primary Educational Service Area 2 and 2) to compare the role of school administrators in promoting quality assurance within the educational institutions of small schools according to teachers’ opinions under the office of Nakhon Ratchasima Primary Educational Service Area 2 classified by status and working experience. The sample group was 172 persons from academic heads or academic teachers and teachers. The tool was a five-rating Likert’s scale questionnaire. The data were analyzed by using percentage, mean, standard deviation, t-test and F-test. The findings were as follows: 1) The role of school administrators in promoting quality assurance within the educational institutions of small schools as whole and in each aspect were in at high level. The first score was the aspect of self-assessment report of schools, then followed by the aspect of quality development according to the educational development plan and the aspect of the development of educational development plan and annual action plan respectively. 2) The comparison of the role of school administrators in promoting quality assurance within the educational institutions of small schools according to teachers’ opinions under the office of Nakhon Ratchasima Primary Educational Service Area 2 classified by status and working experience in overall showed significant difference at 0.05 level.